The Expression Of Cd4+ Lymphocytes Of Bali Cattle After Consuming Mixed Mirerals - Suwiti, Ni Ketut; Windhu, M; Watiniasih, Ni Luh; Besung, I Nengah Kerta; Suartha, I Nyoman (Advances in Tropical Biodiversity and Environmental Sciences; Vol 1 No 2 (2017): ATBESDO - 10.24843/ATBES.2017.v01.i02.p04, 2018)
Minerals play an important role in activating the lymphoid cells. Mineral deficiency can cause interference prolifrasi in lymphocytes, particularly the expresion of CD4 +. Bali cattle are hardly given additional mineral due to cattles are in semi-intensive breeding method. Therefore, this study aims to determine the expression of CD4 + lymphocytes Bali cattle after consuming of mixed mineral. The samples used were 32 male bali cattles reared in the village of Catur, Kintamani, Bangli regency. Samples were divided into 2 groups, those were: 16 individul of bali cattle was given 7.5gr additional of  mixed mineral per individual / day, and theother 16 individual as acontrol. The treatmnes were conducted for 3 months. The results showed that administration of 7.5gr mixed mineral per individual/day did not show differences in the expression of CD4 + lymphocyte of bali cattle.